Morpho–functional monitoring of the esophagus status as the base for the dispenser observation in the patients with achalasia of cardia after surgical esophagocardiomyotomy - S. D. Myasoyedov; S. A. Andreieshchev (Клінічна хірургія, 2021)
Objective. To improve the early diagnosis of complications, occurring after esophagocardiomyotomy in the patients, suffering achalasia of cardia, and their correction, using the early dispenser examination, which have included endoscopic and timed roentgenographic esophageal investigations.